Ru single atoms in Mn2O3 efficiently promote the catalytic oxidation of 5-hydroxymethylfurfural through dual activation of lattice and molecular oxygen - Peiya Chen; Xinghao Li; Yuhan Liu; Huai Liu; Rui Zhang; Wenlong Jia; Junhua Zhang; Yong Sun; Lincai Peng (Green Energy & Environment, 2025)
Concurrent activation of lattice oxygen (OL) and molecular oxygen (O2) is crucial for the efficient catalytic oxidation of biomass-derived molecules over metal oxides. Herein, we report that the introduction of ultralow-loading of Ru single atoms (0.42 wt%) into Mn2O3 matrix (0.4%Ru–Mn2O3) greatly boosts its catalytic activity for the aerobic oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). The FDCA productivity over the 0.4%Ru–Mn2O3 (5.4 mmolFDCA gcat−1 h−1) is 4.9 times higher than the Mn2O3. Especially, this FDCA productivity is also significantly higher than that of existing Ru and Mn-based catalysts. Experimental and theoretical investigations discovered that the Ru single atom facilitated the formation of oxygen vacancy (Ov) in the catalyst, which synergistically weakened the Mn–O bond and promoted the activation of OL. The co-presence of Ru single atoms and Ov also promote the adsorption and activation of both O2 and HMF. Consequently, the dehydrogenation reaction energy barrier of the rate-determining step was reduced via both the OL and chemisorbed O2 dehydrogenation pathways, thus boosting the catalytic oxidation reactions.